Using Locally Resonant Meta-basement to Attenuate Seismic Induced Vibrations of High-rise Buildings - Zhou, Wen (Curtin University, 2025)
This thesis investigates the use of seismic metamaterials for vibration control in high-rise buildings. It begins with the development of a novel meta-basement design that balances performance and cost. The design is further enhanced by incorporating negative stiffness mechanisms and multiple resonators to achieve a wide bandgap in the low-frequency range. Finally, the research extends the symmetric model to consider asymmetry, examining the bandgap characteristics of asymmetric meta-basements with coupled translational-torsional responses.